Automated fire extinguishing system with GSM alarm - Shams, Rafat; Ahmed, Shafkat; Priyom, Shaoni; Fatema, Nusrat (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.